Low Levels of Free Testosterone Correlated with Bone Mineral Densities of Femoral Necks in Aged Healthy Shanghainese Men - Bo, T.; Zhu, J. M. (Hormone and Metabolic Research, 2014)
The aim of the study was to investigate the influence of serum testosterone concentrations on bone mineral densities (BMDs) in healthy aged men in Shanghai area. Eighty-four participants, registered in the physical examination center of our hospital were included. Liquid chromatography tandem mass spectrometry (LC-MS/MS) was used to measure concentrations of total testosterone (TT) and free testosterone (FT) in serum. BMDs of the lumbar spine, femoral neck, the trochanter major, and Ward’s triangle were determined with dual energy X-ray absorptiometry (DXA). The correlations of TT and FT with BMDs at the different skeleton sites were analyzed; stratified analyses by age were performed with 10-year range groups and the changing trends of TT and FT with increasing age were further investigated. In addition, we performed a stratified quartile TT and FT analysis of their correlations with BMDs of different bones in each group. The average age of the participants was 71.8±9.6 years (50–90 years). In a stratified analysis by age, no significant TT changes with increasing age was found, but there was a significant decrease of FT in men older than 80 years (p<0.05). In a stratified FT quartile analysis, FT in the first quartile group correlated significantly with BMDs of the lumbar spine, femoral neck and Ward’s triangle; however, there was only a significant correlation between FT and BMD of the femoral neck after adjustment for age and body mass index (BMI). FT blood serum concentrations decreased significantly in healthy men aged over 80 and positively correlated with BMDs of femoral necks.
Keywords: LC-MS/MS; total testosterone; free testosterone; bone mineral density; X-ray absorptiometry